Vision Loss in the Elderly: Focus on Giant Cell Arteritis (Clinical Observation) - A. V. Novikova; E. I. Schmidt; N. A. Bakunina; A. D. Bogdanova; A. A. Kosheleva (Oftalʹmologiâ)
Introduction: Giant cell (temporal) arteritis (GCA) is a cell-mediated vasculitis that damages the major blood vessels such as an aorta with its major branches and mainly extracranial branches of the carotid artery. Vision loss that can be caused by the anterior ischemic optic neuropathy (AION) or by the central retinal artery occlusion (CRAO) is considered to be one of the most terrible complications of the GCA. In the represented clinical case the complete vision loss was the cause of hospitalization of the patient and the basis for a diagnosis of GCA at the same time. The episodes of the reversible visual impairment that were observed 9 days before the hospitalization attract attention to themselves.Purpose. to pay attention to the main ophthalmological and general symptoms that let the doctor to suspect this disease during the primary reception and to carry out diagnostics promptly to start timely treatment.Conclusion. The main criteria for diagnosis of GCA in the practice of ophthalmologists are female gender, age over 50 years, intense headache with paresthesia, pain in the lower jaw during chewing and short-term episodes of vision loss. Clinical blood test including erythrocyte sedimentation rate, C-reactive protein level and platelet count are the necessary laboratory diagnostic methods.